Educating library and information science students for an ethical information age (2019)
Library and Information Science (LIS) students use information materials for their academic activities. However, in this information age, LIS students are faced with information overload, but are expected to use information appropriately. The way LIS students behave in the use of information is referred to as ethical behaviour. Students that abide by rules and ethics of a profession will behave ethically good, while those that exhibit behaviours that do not abide by such rules and ethics are said to have unethical behaviour. Students behave unethically in ways such as academic dishonesty, plagiarism, cheating, copying and infringement of copyright and should, therefore, acquire ethical knowledge and imbibe such to facilitate their job performance after graduation. Studies have revealed that ethics can be taught as a topic within a course, or throughout the LIS curriculum. The article investigated the ethical behaviour of students, why students should be educated on ethical behaviour, and ways of educating students on ethical behaviour. The acquisition of ethical behaviour to LIS students can be provided by lecturers and library and information professionals on a regular basis.